Ethnic disparities in degree performance - Aslan Zorlu (Institute for the Study of Labor (IZA), 2011)
Using unique administrative individual data, this paper examines ethnic differences in degree performance in Dutch colleges and universities. The paper estimates parametric duration models and accounts for unobserved heterogeneity to assess the sources of ethnic disparities. The analysis shows that ethnic minorities from non-western countries have a significantly lower degree performance and higher risk of dropping-out. Especially, Turkish, Moroccan and Caribbean students are less likely to graduate, and graduates among them need much more time to complete their study. There is no evidence that this disadvantage stems from poor parental socioeconomic position and the choice of study subject.
urn:nbn:de:101:1-2012010913789
Keywords: I23; I24; J15; 330; tertiary education; drop-out; Studierende; Ethnische Gruppe; Bildungsabschluss; Abbrecher; Niederlande